Validation of an electronic jump mat - O'Caireallain, A.; Kenny, I. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this investigation was to determine the validity of a commonly used Electronic Switch Mat (ESM), or jump mat, compared to force platform data. 10 subjects completed 3 Squat Jumps (SJ), 3 Countermovement (CMJ) jumps and 3 Drop Jumps (DJ) from a height of 30cm. The jumps were performed on a force platform (FP) with an ESM positioned on top of the platform. CMJ (r=0.996) and SJ (r=0.958) jump heights correlated very strongly with force platform data however drop jump data was not as strong (r=0.683). The ESM can accurately calculate CMJ height, and SJ height. However, the faster contact times, and rapid movements involved in a DJ may limit its reliability when giving measures of contact time, flight time, and height jumped for DJs.